The phase 3 DUO trial: duvelisib vs ofatumumab in relapsed and refractory CLL/SLL - Flinn, Ian W.; Hillmen, Peter; Montillo, Marco; Nagy, Zsolt; Illés, Árpád; Etienne, Gabriel; Delgado, Julio; Kuss, Bryone J.; Tam, Constantine S.; Gasztonyi, Zoltán; Offner, Fritz; Lunin, Scott; et al. (Blood, 2018)
Duvelisib (also known as IPI-145) is an oral, dual inhibitor of phosphatidylinositol 3-kinase δ and γ (PI3K-δ,γ) being developed for treatment of hematologic malignancies. PI3K-δ,γ signaling can promote B-cell proliferation and survival in clonal B-cell malignancies, such as chronic lymphocytic leukemia (CLL)/small lymphocytic lymphoma (SLL). In a phase 1 study, duvelisib showed clinically meaningful activity and acceptable safety in CLL/SLL patients. We report here the results of DUO, a global phase 3 randomized study of duvelisib vs ofatumumab monotherapy for patients with relapsed or refractory (RR) CLL/SLL. Patients were randomized 1:1 to oral duvelisib 25 mg twice daily (n = 160) or ofatumumab IV (n = 159). The study met the primary study end point by significantly improving progression-free survival per independent review committee assessment compared with ofatumumab for all patients (median, 13.3 months vs 9.9 months; hazard ratio [HR] = 0.52; P < .0001), including those with high-risk chromosome 17p13.1 deletions [del(17p)] and/or TP53 mutations (HR = 0.40; P = .0002). The overall response rate was significantly higher with duvelisib (74% vs 45%; P < .0001) regardless of del(17p) status. The most common adverse events were diarrhea, neutropenia, pyrexia, nausea, anemia, and cough on the duvelisib arm, and neutropenia and infusion reactions on the ofatumumab arm. The DUO trial data support duvelisib as a potentially effective treatment option for patients with RR CLL/SLL. This trial was registered at www.clinicaltrials.gov as #NCT02004522. •Duvelisib significantly improved progression-free survival and overall response rates compared with ofatumumab in RR CLL/SLL patients.•Duvelisib's efficacy and manageable safety profile support its consideration as a novel, oral monotherapy for RR CLL/SLL patients. [Display omitted]